The Effect of Assurance and Emphaty on Customer Satisfaction of Bank Syariah Indonesia (BSI) at Thursina Hospital in Duri City - Makruflis Makruflis (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2022)
This study aims to determine customer satisfaction regarding mobile banking services. This study uses quantitative associative causal relationship (cause and effect). The population of this study were BSI customers at the hospital. Thursina as many as 111 customers. The sampling technique used purposive sampling totaling 87 respondents. Data collection techniques in this study using questionnaires and literature (library study). The data analysis method uses multiple linear regression analysis with IBM SPSS Statistic Version 22 software. The results of this study indicate thatassurance has a positive effect on BSI customer satisfaction at the hospital. Thursina with a significancy 0.000 0.05. while empathy has no effect on customer satisfaction with a significancy 0.051 0.05.